2009
DOI: 10.1007/s11249-009-9515-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Cu Lubrication Additive on the Contact Fatigue Behavior of Steel

Abstract: Effects of four different concentrations of nano-Cu lubrication additives on contact fatigue properties of GCr15 steel friction pairs were evaluated on a ball-rod contact fatigue tester. The anti-fatigue mechanisms of these additives were analyzed by means of scanning electron microscopy and X-ray photo electron spectroscopy. The test results and analyses show that all of these additives can raise the contact fatigue life of steel ball elements to a certain extent. The action of 10% additive is the better. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…Some of the lubricant additives that have been studied include nanoparticles of metals [5,6], metal oxides [7,8], metal sulfides [9,10], rare earth compounds [11], etc. In many of these cases significant improvements to the tribological properties of the lubricants have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the lubricant additives that have been studied include nanoparticles of metals [5,6], metal oxides [7,8], metal sulfides [9,10], rare earth compounds [11], etc. In many of these cases significant improvements to the tribological properties of the lubricants have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Because the tribological mechanism of nanoparticles using as lubricant additives is very different from that of traditional AW and EP additives, which need to react with a rubbing surface to form protecting films (Margielewski et al, 2012;Nicholls et al, 2005), the nanoadditives do not need tribo-active elements such as phosphorus and sulfur in principle (K. Lee et al, 2009). In particular, copper (Cu) nanoparticles are of extraordinary significance, as they can deposit on rubbing surfaces to effectively improve the tribological properties of the base oil, resulting in drastically reduced friction and wear as well as self-repair of worn surfaces (Tarasov and Belyaev, 2004;Tarasov et al, 2002a;Yidong, 2012;Zhang et al, 2009a;Zhang et al, 2009;Zhou et al, 1999Zhou et al, , 2000. Nevertheless, Cu nanoparticles have poor compatibility with base oils and are liable to oxidation, which highly limits their practical use as novel lubricant additives.…”
Section: Introductionmentioning
confidence: 99%
“…In the mean time, the WSD of OA was about 0.65 mm as an additive at a concentration of 0.5 wt.%, being higher than that of modified Cu/rGOA. Some investigators suggested that the modified composites possess a more effective improvement of anti-wear capacity of base oil, owing to the synergetic of Cu/rGOA and OA, as compared with the single modifier [19]. The SEM micrographs of the wear scares which lubricated PAO and PAO containing Cu/rGO composites at the load of 490 N are given in Fig.13.…”
Section: Friction and Wear Properties Of Oa Modified Cu/rgo Compositesmentioning
confidence: 99%
“…Due to the excellent tribological properties of Cu nano-particles and graphene nano-sheets, together with good self-repair functions to the worn surface, and remarkable environmental-friendly property of Cu nano-particles, Cu/rGO composites have been desired for a good candidate for traditional lubricant additives [19]. Different methods were used to synthesis Cu/rGO nanoparticles or graphene/Cu nanoparticals, such as thermal decomposition, CVD-grown, hydrothermal and electrochemical reduction and chemical reduction [20][21][22].…”
mentioning
confidence: 99%